Harry Potter and the deathly hallows 2-film collection [videorecording (Blu-Ray)] . Year 7, parts 1 & 2. - Yates, David, 1963-; Radcliffe, Daniel, 1989-; Grint, Rupert, 1988-; Watson, Emma, 1990-; Rowling, J. K. ([publisher not identified], 2018)
Harry Potter and his friends leave Hogwarts to search for the Horcruxes that will destroy Lord Voldemort, and in the process learn about the magical items known as the Deathly Hallows; Harry and his friends return to Hogwarts to confront Voldemort and his followers using the power of the Deathly Hallows.